Task-shifting for cardiovascular risk factor management: lessons from the Global Alliance for Chronic Diseases. (8th November 2018) - Joshi, Rohina; Thrift, Amanda G; Smith, Carter; Praveen, Devarsetty; Vedanthan, Rajesh; Gyamfi, Joyce; Schwalm, Jon-David; Limbani, Felix; Rubinstein, Adolfo; Parker, Gary; Ogedegbe, Olugbenga; Plange-Rhule, Jacob; et al.
Abstract : Task-shifting to non-physician health workers (NPHWs) has been an effective model for managing infectious diseases and improving maternal and child health. There is inadequate evidence to show the effectiveness of NPHWs to manage cardiovascular diseases (CVDs). In 2012, the Global Alliance for Chronic Diseases funded eight studies which focused on task-shifting to NPHWs for the management of hypertension. We report the lessons learnt from the field. From each of the studies, we obtained information on the types of tasks shifted, the professional level from which the task was shifted, the training provided and the challenges faced. Additionally, we collected more granular data on 'lessons learnt ' throughout the implementation process and 'design to implementation' changes that emerged in each project. The tasks shifted to NPHWs included screening of individuals, referral to physicians for diagnosis and management, patient education for lifestyle improvement, follow-up and reminders for medication adherence and appointments. In four studies, tasks were shifted from physicians to NPHWs and in four studies tasks were shared between two different levels of NPHWs. Training programmes ranged between 3 and 7 days with regular refresher training. Two studies used clinical decision support tools and mobile health components. Challenges faced included system level barriers such as inability to prescribe medicines, varying skill sets of NPHWs, high workload and staff turnover. With the acute shortage of the health workforce in low-income and middle-income countries (LMICs), achieving better health outcomes for the prevention and control of CVD is a major challenge. Task-shifting or sharing provides a practical model for the management of CVD in LMICs.